2023
DOI: 10.1108/dprg-04-2023-0053
|View full text |Cite
|
Sign up to set email alerts
|

A study on blockchain-based marketplace governance platform adoption: a multi-industry perspective

Kumar Saurabh,
Parijat Upadhyay,
Neelam Rani

Abstract: Purpose Decentralised autonomous organisations (DAOs) are internet-native self-governing enterprises where individual groups, communities, agencies, consumers and providers work together using blockchain-led smart contracts (SCs). This study aims to examine the role of DAO marketplaces in technology-led autonomous organisation design for enterprise technology sourcing industries, with algorithmic trust and governance. Design/methodology/approach The authors examined the importance of an enterprise marketplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Saurabh et al (2023a) proposed digital business model canvas elements for DAOs. Saurabh et al (2023b) proposed a DAO-based solution for an enterprise marketplace. The results showed that such a solution can provide a cohesive collaboration between stakeholders, without relying on any third-party.…”
Section: Related Workmentioning
confidence: 99%
“…Saurabh et al (2023a) proposed digital business model canvas elements for DAOs. Saurabh et al (2023b) proposed a DAO-based solution for an enterprise marketplace. The results showed that such a solution can provide a cohesive collaboration between stakeholders, without relying on any third-party.…”
Section: Related Workmentioning
confidence: 99%
“… Data Governance, Surveillance, and IT [ 63 , 64 , 16 , 65 , 66 , 67 ] •Data governance using BCT ensures data privacy by providing a single shared ledger to service providers. Business and Corporate Governance [ 68 , 69 , 70 , 71 , 72 , 73 , [74] , [75] , [76] , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ] •Blockchain reduces the need for mediators, eases the exchange of documents and removes third party verification in supply chain management. •In corporate governance, BCT reduces proxy voting and assists in decision making for company shareholders.…”
Section: Thematic Analysismentioning
confidence: 99%